Re-establishment Singular Spectral Problem by Nodal Data - Bas, Erdal; Panakhov, Etibar S.; Ozarslan, Ramazan (Amer Inst Physics, 2016)
In this study, we are concerned with singular Sturm-Liouville Problem by using a new kind of spectral data that is known as nodal points. We obtain some asymptotic results about the problem. Furthermore, we prove a re-establishment formula for singular potential.
International Conference on Advances in Natural and Applied Sciences (ICANAS) -- APR 21-23, 2016 -- Antalya, TURKEY
Keywords: Sturm; Reconstruction